2012
DOI: 10.1016/j.jmb.2011.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Slow Amyloid Nucleation via α-Helix-Rich Oligomeric Intermediates in Short Polyglutamine-Containing Huntingtin Fragments

Abstract: The 17-amino-acid N-terminal segment (httNT) that leads into the polyglutamine (polyQ) segment in the Huntington's disease protein huntingtin (htt) dramatically increases aggregation rates and changes the aggregation mechanism, compared to a simple polyQ peptide of similar length. With polyQ segments near or above the pathological repeat length threshold of about 37, aggregation of htt N-terminal fragments is so rapid that it is difficult to tease out mechanistic details. We describe here the use of very short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

38
392
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 176 publications
(433 citation statements)
references
References 74 publications
38
392
3
Order By: Relevance
“…Because the suppressors greatly increased the total accumulation of Htt103Q, our PrD suppressors must prevent the formation of oligomers and/or promote their sequestration. PolyQ-expanded Htt exon-1, in vitro, forms an α-helical oligomer early in the aggregation process (40). It is possible that the suppressor PrDs intercalate into such α-helix-rich oligomers and promote their assembly into the large coaggregated foci.…”
Section: Discussionmentioning
confidence: 99%
“…Because the suppressors greatly increased the total accumulation of Htt103Q, our PrD suppressors must prevent the formation of oligomers and/or promote their sequestration. PolyQ-expanded Htt exon-1, in vitro, forms an α-helical oligomer early in the aggregation process (40). It is possible that the suppressor PrDs intercalate into such α-helix-rich oligomers and promote their assembly into the large coaggregated foci.…”
Section: Discussionmentioning
confidence: 99%
“…40,41 CD spectra and molecular dynamics simulations 42 suggest that the N-terminal sequence by itself has a tendency to take on some α-helical secondary structure, while expanded polyQ was shown to aquire a β-sheet conformation. 43 Formation of amyloid-like fibrils with β-sheet structure is observed with many protein sequences and is linked to many neurodegenerative conditions, including Parkinson, Huntington and Alzheimer diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The NT17 tract has been shown to be critical for the formation of α-helix-rich oligomeric intermediates by Jayaraman et al (14). We, therefore, first construct the aggregation free energy profile for six NT17-Q20 monomers in a simulation box at the nominal laboratory concentration of the study by Wetzel (19).…”
Section: N-terminal Region Facilitates the Aggregation Of Nt 17 -Q 20mentioning
confidence: 99%
“…Structural characterization of the aggregates (13,14,(18)(19)(20) has shown that, even when there are flanking sequences, polyQ remains the fiber core and adopts a β-hairpin conformation. In this paper, we use energy landscape analysis to provide a detailed molecular picture of the aggregation process of the peptide encoded by HTT exon 1, focusing on how the flanking sequences influence aggregation.…”
mentioning
confidence: 99%
See 1 more Smart Citation